Conflict Resolution of Inheritance Disputes in The Koto Nan Ampek Village of Payakumbuh City - Febrian Martha; Febri Yulika; Endrizal (Kirana Publisher (KNPub), 2023)
This study discusses the problem of community conflict related to inheritance disputes that occurred in Kanagarian Koto Nan Ampek, Payakumbuh City. The purpose of this study is to explain the background of the conflict in Kanagarian Koto Nan Ampek and the resolution given based on the conflict that has arisen. The theory used is Lewis A. Coser's theory of conflict. The method used is qualitative research with an ethnographic approach. Data collection techniques are field observations, interviews, and documentation. The findings of this study are the conflict over inheritance disputes that occurred in Kanagarian Koto Nan Ampek caused by several factors including the lack of knowledge of the heirs regarding the inheritance, the allotment of inheritance which is not known jointly, socially and economically. The impact of this is that there is a change in the character of the Koto Nan Ampek community towards inheritance, which previously guarded inheritance, changed to selling heirlooms. Then there are several solutions offered based on the factors causing the conflict, namely education by traditional institutions or people who know about inheritance, written agreements, and deliberations for consensus.